Association of the Work Schedules of Hospitalists With Patient Outcomes of Hospitalization - Goodwin, James S. (JAMA Intern Med, 2019)
IMPORTANCE: The working schedules of hospitalists vary widely. Discontinuous schedules, such as 24 hours on and 48 hours off, result in several hospitalists providing care during a patient’s hospital stay. Poor continuity of care during hospitalization may be associated with poor patient outcomes. OBJECTIVE: To determine whether admitted patients receiving care from hospitalists with more discontinuous schedules experience worse outcomes. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort study used conditional models to assess Medicare claims data for 114 777 medical admissions of patients with a 3-day to 6-day length of stay from January 1, 2014, through November 30, 2016, who received all general medical care from hospitalists in 229 hospitals in Texas. Data were analyzed from November 2018 to June 2019. EXPOSURES: For each admission, the weighted mean of schedule continuity for the treating hospitalists, assessed as the percentage of all their working days in that year that were part of a block of 7 or more consecutive working days, was calculated. MAIN OUTCOMES AND MEASURES: The primary outcome was patient mortality in the 30 days after discharge. Secondary outcomes were readmission rates and Medicare costs in the 30 days after discharge, and discharge destination. RESULTS: Of the 114 777 patient admissions, the mean (SD) age was 79.9 (8.3) years, and 70 047 (61.0%) were women. For admissions in the lowest quartile for continuity of hospitalist schedules, the hospitalists providing care worked 0% to 30% of their total working days as part of a block of 7 or more consecutive days vs 67% to 100% for hospitalists providing care for patients in the highest quartile for continuity. Patient characteristics were not associated with the continuity of working schedules for the hospitalist(s) providing care. In conditional logistic regression models, admitted patients cared for by hospitalists in the highest quartile of schedule continuity (vs the lowest quartile) had lower 30-day mortality after discharge (adjusted odds ratio [aOR], 0.88; 95% CI, 0.81-0.95), lower readmission rates (aOR, 0.94; 95% CI, 0.90-0.99), higher rates of discharge to the home (aOR, 1.08; 95% CI, 1.03-1.13), and lower 30-day postdischarge costs (−$223; 95% CI, −$441 to −$7). The results were similar across a range of different methods for defining continuity of hospitalist schedules and selecting the cohort. CONCLUSIONS AND RELEVANCE: Hospitalist schedules vary widely. Admitted patients receiving care from hospitalists with schedules that promote inpatient continuity of care may experience better outcomes of hospitalization.